2013
DOI: 10.1371/journal.pcbi.1003245
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding T Cell Calcium Response Diversity with Methods for Automated and Accurate Analysis of Cell Signals (MAAACS)

Abstract: We introduce a series of experimental procedures enabling sensitive calcium monitoring in T cell populations by confocal video-microscopy. Tracking and post-acquisition analysis was performed using Methods for Automated and Accurate Analysis of Cell Signals (MAAACS), a fully customized program that associates a high throughput tracking algorithm, an intuitive reconnection routine and a statistical platform to provide, at a glance, the calcium barcode of a population of individual T-cells. Combined with a sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 78 publications
2
66
0
Order By: Relevance
“…Additionally, the Ca 2+ intensity amplitude and Ca 2+ intensity peak width is also provided by CalQuo 2 (see Supplementary Information). By analyzing the response function in Fourier space, CalQuo 2 is robust against noise in the raw data, offering improved performance over algorithms based on a single threshold 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Ca 2+ intensity amplitude and Ca 2+ intensity peak width is also provided by CalQuo 2 (see Supplementary Information). By analyzing the response function in Fourier space, CalQuo 2 is robust against noise in the raw data, offering improved performance over algorithms based on a single threshold 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently developed highly sophisticated feature-based methods can take fluorescent image files of populations of cells as their inputs, and return statistical analyses that incorporate both spatial and temporal information from the experimental measurements into their assessments of calcium dynamics [12, 35, 36]. Our Markovian Information Entropy method is currently restricted to the subset of the analysis process which converts a calcium activity time series into a single numerical value for downstream analysis, and so any upstream image processing or downstream statistical analysis must be conceived and performed by the experimenter.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to continuously track single cell's Ca 2+ responses over time is advantageous over flow cytometry, and has allowed a greater appreciation of Ca 2+ ‐dependent pathways 75 , 76 . We and others have shown that flow cytometry is unable to decipher the extent of activation, as calculated by the frequency of responding cells that are contributing to the overall response 75 , 77 , 78 . By using single‐cell analysis coupled to fluorescence microscopy, the information encoded in heterogeneous oscillations can be expressed by several parameters such as those observed by flow cytometry, including mean, peak concentration or fluorescence ratio and the change in fluorescence ratio 79 , 80 , 81 , 82 .…”
Section: Quantifying Heterogeneous Calcium Responsesmentioning
confidence: 99%